A 150-Year-Old Kuril Islands Tragedy: Yet Another Solution to the Copper Island Aleut Enigma - Chlenov, M.A. (Études Inuit Studies, 2021)
The paper focuses on the origins of the peculiar contact variant of the Aleutian language spoken on Medny or Copper Island in the Commander Islands. Russian linguists and anthropologists managed to study and record this unusual language in the final stage of its existence, defining it not as a pidgin or a creole language, as might reasonably have been assumed, but as a peculiar “mixed” language, in which the lexical material had an Aleutian (Attuan) origin while the verbal paradigm and inflectional morphemes were Russian, and the derivational morphemes were Aleutian. Today, the Medny Aleutian language is on the verge of extinction, with only five speakers having been recorded in 2004. It is quite possible that this language has since fallen completely out of use. But it was nevertheless a huge achievement that scholars documented it, studied its structure and vocabulary, and wrote down texts literally on the eve of its disappearance. The problem, however, lies in its unusual character, that of a reverse “mirror-image” of a creole language, where one would expect Russian vocabulary with elements of Aleutian morphology rather than the reverse situation, which is actually the case. Accordingly, the question of its origin remains unresolved. The author of the paper compiled full genealogical trees of the Commander Aleuts, making it possible to trace the process of settling the islands at the family and individual level. In other words, he set himself the task of finding that Russian-speaking population on Medny Island for which the socially dominant and reference population, existing alongside it on the same territory and engaged in the same economic activity, would be native speakers of the Attuan dialect of Aleutian. Otherwise, one would have expected the emergence of a kind of “pidgin Russian,” in which Russian vocabulary would be used with elements of Aleutian morphology, or with the morphological constructions that generally characterize pidgin and creole languages. In the case of Copper Island, however, as linguists note, we are faced not with a “Russian pidgin” but an “Aleutian pidgin”.